User-Centered evaluation of an On-Line modern greek language course - Zaphiris, Panayiotis; Zacharia, Giorgos (My University, 2001)
In this paper, a set of user-centered evaluation methods, used to construct a richer conception of the audience of an online Modern Greek online course, are presented. First an analysis of the design methodology employed in this specific case study is provided and then examples of how valuable usability information can be extracted from different user-center evaluation methods is presented. Conclusions, related to the analysis of the information obtained through the different evaluation methods and about the usability of the course, are also provided.